Greywater use for food security in refugee camps: a guidance note for risk management - Drechsel, Pay (International Water Management Institute, 2024)
In contexts of forced displacement where freshwater access is limited, greywater reuse offers an opportunity to support small-scale irrigation and improve food and nutrition security. While greywater quality is higher than that of combined wastewater, it still carries microbial and chemical risks, particularly in overcrowded camps with poor sanitation. Safe reuse depends on separating greywater from blackwater, using nature-based treatment methods such as gravel beds or constructed wetlands, and implementing multiple safety barriers ranging from crop selection and irrigation techniques to hygiene education and food preparation practices. Household-level interventions like keyhole gardens and vertical sack farming have proven effective in space-constrained environments, allowing nutrient-rich greywater to be reused while minimizing human contact. Health risks can be reduced through subsurface irrigation, withholding periods, and disinfection, though excessive use of chlorine may harm soils and crops. The report emphasizes tailoring reuse strategies to local housing types, resource availability, and user capacity. Stakeholder engagement, especially among women, is essential for crop choices, risk mitigation, and long-term maintenance. Environmental safeguards, vector control, and context-specific decision tools are needed to ensure that greywater reuse enhances resilience without compromising public or ecological health.